PAW27 Age-dependent phenotypic variation of multiple sclerosis at disease onset. Issue 11 (22nd October 2010) - Cossburn, M; Hirst, C L; Pickersgill, T P; Robertson, N P; Ben-Shlomo, Y; Ingram, G
Abstract : Clinical details of disease onset in multiple sclerosis (MS) are valuable, providing insight into disease outcome. Age is recognised as an important modifying factor for prognosis and may also exert an effect on characteristics of disease ignition. Understanding age-specific presentations improves interpretation of early disease, informing future management and may identify groups of patients with distinct clinical features. Using prospective data gathered over more than 20 years we have examined associations between age and clinical features at onset in 1207 patients from the UK, making specific comparisons between childhood and late-onset multiple sclerosis (LOMS). Age at onset varied significantly between sexes (M:32.2, F:29.8), 0.6% had paediatric, 2.9% adolescent and 4.0% LOMS. Only 6% had a progressive disease from onset (PPMS). F:M ratios were highest <16 years of age and reversed over the age of 50 (1:1.3). Ataxia at onset was common in the young but fell rapidly after age 30. Sphincteric, lower limb and facial motor symptoms rose with age independent of disease course. Probability of complete recovery from first event declined with age from 84% to 39.6% (p>0.001). Age at disease onset in MS exerts a significant effect on sex ratios, degree of recovery and symptoms. The rate of PPMS is only 6% when recall bias is eliminated. This, together with reducing odds of recovery with age provides little support for the aetiological separation of relapsing and progressive disease.